Developmental biology of peripheral lymphoid organs - Balogh, Peter. (Springer, 2011)
The human immune system is a complex network of tissues and organs dispersed throughout the body. Immunology, as one of the most rapidly evolving fields in biomedical research, has to date covered the essential cellular and molecular events necessary for immune responses to occur, but has paid relatively little attention to important developmental processes underlying the formation of the tissues themselves that carry out immune responses in humans and other mammalians. In contrast to the thymus and bone marrow that generate mature leukocytes for antigen recognition and handling, these latter tissues display broad tissue distribution and possess diverse architectural characteristics. These peripheral lymphoid tissues and organs develop prior to the individual’s exposure to external antigens, and despite their similar functions, their varied appearances indicate a substantial complexity of tissue ontogeny. This volume presents a comprehensive overview of the developmental features of the major peripheral lymphoid organs, thus examining the connection between immunological functionality and structural characteristics utilizing a developmental approach, for an audience ranging from undergraduate students to senior researchers in immunology, histology and clinical medicine. Introduction: Evolution of peripheral lymphoid organs -- Common themes in lymphoid organ development -- Development of lymph nodes in humans and rodents -- Programmed and nascent gut-associated organized lymphoid tissues -- Single complexity: the spleen -- Age-associated decline in peripheral lymphoid organ functions.